Regional neuroinflammation induced by peripheral infection contributes to fatigue-like symptoms: a [18F]DPA-714 positron emission tomography study in rats - Li, Danxi; Hu, Di; Ochi, Yuta; Arakaki, Wakiko; Mawatari, Aya; Shigeta, Mika; Wu, Yuping; Hayashinaka, Emi; Neyama, Hiroyuki; Tahara, Tsuyoshi; Wada, Yasuhiro; Li, Feng; et al. (Frontiers in Immunology, 2023)
Introduction A series of symptoms, including fever, widespread pain, fatigue, and even ageusia, have frequently been reported in the context of various infections, such as COVID-19. Although the pathogenic mechanisms underlying an infection causing fever and pain have been well established, the mechanisms of fatigue induced by infection in specific brain regions remain unclear. Methods To elucidate whether and how the peripheral infection cause fatigue via regional neuroinflammation, we performed a brain-wide investigation of neuroinflammation in a peripheral pseudoinfection rat model using [18F]DPA-714 positron emission tomography (PET) imaging analysis, in which the polyriboinosinic: polyribocytidylic acid (poly I:C) was intraperitoneally injected. Results Transient fever lasting for several hours and subsequent suppression of spontaneous activity lasting a few days were induced by poly I:C treatment. Significant increase in plasma interleukin (IL)-1β, IL-6 and tumour necrosis factor (TNF)-α were observed at 2 and 4 h following poly I:C treatment. PET imaging analysis revealed that the brain uptake of [18F]DPA-714 was significantly increased in several brain regions one day after poly I:C treatment, such as the dorsal raphe (DR), parvicellular part of red nucleus (RPC), A5 and A7 noradrenergic nucleus, compared with the control group. The accumulation of [18F]DPA-714 in the DR, RPC and A5 was positively correlated with subsequent fatigue-like behavior, and that in the A7 tended to positively correlate with fever. Discussion These findings suggest that peripheral infection may trigger regional neuroinflammation, which may cause specific symptoms such as fatigue. A similar mechanism might be involved in COVID-19.